Sophisticated discipline in a nascent deposit market: evidence from post-communist Russia - Alexei Karas; William Pyle; Koen Schoors (Bank of Finland, Institute for Economies in Transition (BOFIT), 2006)
Using a database from post-communist, pre-deposit-insurance Russia, we demonstrate the presence of quantity-based sanctioning of weaker banks by both firms and households, particularly after the financial crisis of 1998.Evidence for the standard form of price discipline, however, is notably weak.We estimate the deposit supply function and show that, particularly for poorly capitalized banks, interest rate increases exhibit diminishing, and eventually negative, returns in terms of deposit attraction.These findings are consistent with depositors interpreting the deposit rate itself as a complementary proxy of otherwise unobserved bank-level risk.
URN:NBN:fi:bof-201408072190
Keywords: G21; O16; P2; 330; market discipline; deposit market; transition; Russia